Influence of structured counseling on women's selection of hormonal contraception in Israel: results of the CHOICE study - Yeshaya A; Ber A; Seidman DS; Oddens BJ (Dove Medical Press, 2014)
Arie Yeshaya,1 Amos Ber,2 Daniel S Seidman,3 Bjorn J Oddens41Department of Obstetrics and Gynecology, Rabin Medical Center, Petah Tikva, 2Maccabi Health Services, Tel Aviv, Israel; 3Department of Obstetrics and Gynecology, Sacker School of Medicine, Tel Hashomer, Israel; 4Global Medical Affairs, MSD, Oss, the NetherlandsBackground: The multinational CHOICE (Contraceptive Health Research Of Informed Choice Experience) study evaluated the effects of structured counseling on women's contraceptive decisions, their reasons for making those decisions, and their perceptions of combined hormonal contraceptive (CHC) methods in eleven countries. The aim of this paper to present data from the 1,802 women participating in Israel's CHOICE program.Methods: Women (aged 17–40 years) who consulted their health care providers about contraception and who would consider a CHC method qualified to participate. After indicating their intended CHC method, the women received counseling about the daily pill, weekly patch, and monthly vaginal ring. After counseling, the women completed a questionnaire about their contraceptive decisions.Results: Before counseling, 67%, 6%, and 5% of women (mean age 27 years) intended to use the pill, patch, or ring, respectively. Counseling significantly influenced the women's CHC choice, with 56%, 12%, and 23% of women selecting the pill, patch, or ring (P<0.0001 for all contraceptive methods versus before counseling). Logistic regression analysis suggested that age significantly increased the probability of switching from the pill to the ring.Conclusion: Although the pill was the most popular choice overall, counseling appeared to influence Israeli women's contraceptive decisions, with significantly more women selecting the patch. More than four times as many women selected the ring after counseling than before counseling.Keywords: combined hormonal contraceptive, counseling, contraceptive ring, contraceptive patch, oral contraceptive pill